PENGARUH VISUAL MERCHANDISING DAN PRODUCT ASSORTMENT TERHADAP IMPULSE BUYING (Survei Pada Konsumen Rabbani Kota Sukabumi) - Firdayanti, Nuri; Ramdan, Asep Muhamad; Sunarya, Erry (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aims to study the effect of visual merchandising and product assortment on impulse buying. The data analysis technique used is a double linear regression analysis with sample techniques using non-probability sampling samples by incidental sampling method. Data collection by spreading questionnaire to 150 respondents. Data processing using IBM SPSS software version 24. Results showed that simultaneously visual merchandising and product assortment effect positive and significant to impulse buying. A partial test shows the visual merchandising effect positively and significantly on impulse buying. While the product assortment influential but not significant to impulse buying